Hubungan Bimbingan Kelompok dengan Motivasi Belajar Siswa SMP Negeri 5 Rambah Kabupaten Rokan Hulu Provinsi Riau - H. Hasbi (Instructional Development Journal, 2018)
In writing this article the writer chooses research with the title of Relationship Guidance Group with Learning Motivation for Students of SMP Negeri 5 Rambah, Rokan Hulu Regency, Riau Province. This article aims to describe the learning motivation of students in SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province; describe the implementation of guidance for groups of SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province; and know whether or not there is a relationship between students' learning motivation with the guidance of the group of SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province. This article discusses two variables, namely group guidance and learning motivation. The population in this study were students of SMP Negeri 3 Rambah Hilir Academic Year 2013/2014 which amounted to 82 students consisting of three classes. The sample that will be used in this study is SMP Negeri 3 students which are Downstream in 2013/2014 Academic Year with a total of 82 students. The sampling technique used by researchers is a sample consideration. What is meant by sample consideration is in taking the sample, researchers take samples based on certain considerations. This sampling is based on consideration at the highest class average. So the research made the VIIA class as a research sample as many as 29 students. The type of research used in this study is expost facto research or referred to after after the fact. Data collection techniques used are documentation, observation, and questionnaire.Based on the calculation results obtained that the significance value is 0,000 which is smaller than the value of a = 0.05 and the calculated value is 0.599 ** in the "moderate" category. The price of the coefficient is then tested for significance by comparing the table for n = 80 at the level of 5%, then table = 0.220, where the value of r count> r table (0.599> 0.220) and the significance value obtained is less than 0.05. Thus, Ha is accepted, that is, there is a relationship between group guidance services and Learning Motivation for class VIII students of SMP Negeri 5 Rambah Hilir, Rokan Hulu Regency, Riau Province. While the contribution of group guidance services in improving student learning motivation is 35.88%.